Promoting creative economies in Nigeria and South Africa through communal and collaborative intellectual property rights strategies - Chuma-Okoro, Helen (Department of Commercial Law, 2022)
The contention against and for extending intellectual property rights (IPRs) to traditional cultural expressions (TCEs) is strong on both sides: on one hand IPRs remain largely incompatible with TCEs and inadequate for safeguarding them. On the other hand, TCEs need protection in the interest of both the knowledge and their owners. The main challenges for Nigeria and South Africa as developing African countries in harnessing the benefits of their creative economy by exploiting the potential of their TCEs, particularly tradition-based arts and crafts, are tied to these contentions. IPRs remain the dominant framework for reaping the benefits of the creative economy; yet there are conceptual and practical challenges in applying IPRs to fully exploit the economic values of TCEs. Adopting a desktop and library-based research approach, this thesis seeks to resolve this dilemma by relying instead on alternative interpretations of narratives that underpin the dilemma, to justify the protection of tradition-based resources via IPRs. It also relies on the utilitarian outcomes from exploiting TCEs as valid rationales for the use of IPRs by the two study countries to fully exploit the economic benefits of their tradition-based arts and crafts. It examines how communal IPRs constitute a strong point of convergence between IPR and TCEs in ways that make them compatible and suitable measures to help derive greater benefits from TCEs in the market environment. It highlights the connections between the sector and the creative economy, and the socio-economic benefits of this nexus as justification for promoting, protecting and preserving tradition-based arts and crafts; and the suitability of communal IPRs in achieving these tripartite objectives. It concludes that the extant laws of the two countries do not adequately support the effective use of communal IPRs to achieve the objectives as such, and makes recommendations for addressing the gaps.